Analisis Ergonomi di Lingkungan Kerja Industri Rumah Tangga Kerupuk Ikan Tenggiri Agung Rasa di Cilacap - Anisha Dian Iswahyuni (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
The fish processing industry in Cilacap district is a business that is quite popular, because processed fish is a superior product in Cilacap district, one of which is mackerel fish crackers. This is influenced by the fact that the Cilacap district is a coastal area and is a place for tourist visits so that people's interest in various food flavors is quite high. Ergonomic analysis is needed to create safe, comfortable and healthy working conditions so that work activities can be effective which has an effect on increasing productivity. The method used in this research is descriptive experimental through observation and interview methods. Located in the Agung Rasa mackerel fish cracker home industry. The results of the research obtained an ergonomic analysis using an approach to 8 ergonomic aspects in the form of use of muscle power, work attitude, nutrition, work environment, work time, information systems, socio-cultural conditions and human-machine interaction which is known to still not show ergonomic working conditions. From the results of this analysis, recommendations can be made in the form of implementing short breaks or implementing exercise between work activities to avoid feelings of boredom, fatigue and musculoskeletal complaints, then improvements to work stations, regular working time arrangements and layout arrangements can be implemented to create ergonomic working conditions.